2018
DOI: 10.1016/j.joca.2018.02.387
|View full text |Cite
|
Sign up to set email alerts
|

C1M, C2M, C3M, PRO-C2, and CRPM in serum reflect different potential pathogenetic domains of osteoarthritis, data from check

Abstract: Purpose: The fragment of C-terminal cross-linked telopeptide of type II collagen (CTX-II) is released into circulation and subsequently secreted into urine as a result of articular cartilage degradation in osteoarthritis (OA) disease. The urinary CTX-II (uCTX-II), a competitive immunoassay, has been studied in numerous studies. It is considered as one of the best-validated biomarker in OA field. However, the CTX-II in blood have shown limited value, although there would be some advantages of blood versus urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the Cohort Hip and Cohort Knee (CHECK) cohort of patients with an early OA phenotype and pain in the knee and/or the hip followed for 10 years, principal component analysis showed that serum C3M and serum CRPM levels may reflect different distinct inflammatory domains compared with serum C1M (a marker measuring type I collagen degradation), erythrocyte sedimentation rate, and hsCRP. 93 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Cohort Hip and Cohort Knee (CHECK) cohort of patients with an early OA phenotype and pain in the knee and/or the hip followed for 10 years, principal component analysis showed that serum C3M and serum CRPM levels may reflect different distinct inflammatory domains compared with serum C1M (a marker measuring type I collagen degradation), erythrocyte sedimentation rate, and hsCRP. 93 …”
Section: Methodsmentioning
confidence: 99%
“…In the Cohort Hip and Cohort Knee (CHECK) cohort of patients with an early OA phenotype and pain in the knee and/or the hip followed for 10 years, principal component analysis showed that serum C3M and serum CRPM levels may reflect different distinct inflammatory domains compared with serum C1M (a marker measuring type I collagen degradation), erythrocyte sedimentation rate, and hsCRP. 93 Finally, in a study including 99 patients with erosive and non-erosive hand OA, Fioravanti et al 94 in 2018 found higher serum visfatin levels in erosive hand OA compared with nonerosive hand OA. Visfatin has proinflammatory and immunomodulation functions contributing to cartilage degeneration.…”
Section: Biomarkers To Segregate Oa Patients In Molecular Endotypesmentioning
confidence: 98%
“…Together with C1M and C3M, CRPM, an MMP-dependent degradation of CRP in serum, appears to also reflect tissue inflammation in individuals with knee and/or hip pain likely related to primary OA [ 57 ]. Elevated CRPM has been observed in OA patients with higher C1M and CRP levels, supporting the concept of inflammation in a subset of the OA population [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…No association with CRPM has been found in this study despite high levels being found to be prognostic of incident knee OA [ 50 , 58 ]. As C1M and C3M but not CRPM were found to have associations with BMLs, these biochemical markers may reflect distinct inflammatory domains or niches in OA [ 57 ].…”
Section: Discussionmentioning
confidence: 99%